فاعلية إنفوجرافيك لتنمية الوعي الصحي الوقائي للوقاية من فيروس كورونا وعلاقته بجودة الحياة لدى تلاميذ المرحلة الابتدائية - أحمد، فرج عبده فرج (الجمعية المصرية لتكنولوجيا التعليم, 2021)
استهدف البحث الحالي قياس مدى فاعلية إنفوجرافيك لتنمية الوعي الصحي الوقائي للوقاية من فيروس كورونا، وعلاقته بجودة الحياة لدى تلاميذ المرحلة الابتدائية، ولتحقيق هذا الهدف استخدم الباحث المنهج الوصفي والمنهج الشبه تجريبي، الذي تضمنت إجراءاته إعداد بعض الأدوات البحثية وهي: إعداد مقياس للوعي الصحي الوقائي، بالإضافة إلى إعداد مقياس في جودة الحياة، وقد تم تطبيق تلك الأدوات على عينة البحث والمتمثلة في: عينة عشوائية من تلاميذ المرحلة الابتدائية، من تلاميذ المرحلة الابتدائية وقوامها (30) طالب من الإمام محمد عبده التابعة لإدارة بنها التعليمية بمحافظة القليوبية مقر سكن الباحث. وقد قام الباحث باختيار تصميم تجريبي ذات المجموعة الواحدة وقوامها (30) طالب، يتم فيه تطبيق أدوات البحث سالفة الذكر قبليا وبعديا يتخلل ذلك تقديم المعالجة على عينة البحث والمتمثلة في الإنفوجرافيك، وبعد عملية التطبيق يتم رصد البيانات الناتجة عن هذا التطبيق، وباستخدام برنامج الرزم الإحصائية spss المحوسب، وذلك لاستخراج نتائج البحث، التي أشارت إلى؛ فاعلية الإنفوجرافيك في تنمية كل من الوعي الصحي الوقائي وجودة الحياة لدى تلاميذ المرحلة الابتدائية، وكذلك أثبتت الدراسة العلاقة الموجبة الطردية بين كل من الوعي الصحي الوقائي وجودت الحياة لدى تلاميذ المرحلة الابتدائية. كما أوصي البحث بضرورة تضمين محور المفاهيم والسلوكيات الصحية للوقاية من الأمراض الوبائية بصفة عامة، وفيروس كورونا بصفة خاصة بمناهج التعليم الابتدائي.
The current research aimed to measure the effectiveness of an infographic for developing preventive health awareness to prevent corona virus, and its relationship to quality of life among primary school students, and to achieve this goal the researcher used the descriptive approach and the quasi-experimental approach, whose procedures included the preparation of some research tools, namely: Preparing a measure for preventive health awareness, In addition to preparing a measure in the quality of life, and those tools were applied to the research sample, which is: a random sample of primary school students, from elementary school pupils, consisting of (30) students from Imam Muhammad Abdu of the Benha Education Administration in Qalyubia Governorate, the researcher's residence. The researcher has chosen an experimental design with one group of (30) students, in which the aforementioned research tools are applied before and after, during which the treatment is presented to the research sample represented in the infographic, and after the application process the data resulting from this application is monitored, using a program Computerized spss statistical packages, in order to extract the search results, which indicated; The effectiveness of the infographic in developing both preventive health awareness and the quality of life among primary school students, and the study also demonstrated the positive positive relationship between preventive health awareness and the quality of life among primary school students. The necessity of including the focus of health concepts and behaviors to prevent epidemic diseases in general, and the Corona virus in particular, in the primary education curricula.
Keywords: طلبة المرحلة الابتدائية -- الوعي الصحي الوقائي -- فيروس كورونا (كوفيد-19) -- جودة الحياة -- الإنفوجرافيك -- محافظة القليوبية -- مصر